Do granic tożsamości. O portretach zdwojonych Stanisława Wyspiańskiego - Bałus, Wojciech (Przestrzenie Teorii, 2008)
This text is devoted to double portraits of S. Wyspiański. Macierzyństwo [Motherhood], a portrait of Henryk Opieński and of Eliza Parmeńska becomes for the author an inspiration not only to speak about plastic quality of these works, but also refer to fundamental questions concerning the cognition of human psyche. They also direct the researcher's attention towards such problems as doubling, mirror reflection, or a motif of a lookalike.